Recent Trends in Nanotechnology and Materials Science Selected Review Papers from the 2013 International Conference on Manufacturing, Optimization, Industrial and Material Engineering (MOIME 2013) - Gaol, Ford Lumban; Webb, Jeffrey (Engineering Materials, 2014)
This book presents 8 selected reviews from the 2013 International Conference on Manufacturing, Optimization, Industrial and Material Engineering, held in Bandung, Indonesia, 09-10 March 2013. The chapters focus on new advances and research results in the fields of Nanotechnology and Materials Science, from metals to thin films technology.